2013
DOI: 10.1002/ece3.781
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and dynamics of rapid local adaptation and sex in varying habitat types in rotifers

Abstract: Local adaptation is an important principle in a world of environmental change and might be critical for species persistence. We tested the hypothesis that replicated populations can attain rapid local adaptation under two varying laboratory environments. Clonal subpopulations of the cyclically parthenogenetic rotifer Brachionus calyciflorus were allowed to adapt to two varying harsh and a benign environment: a high-salt, a food-limited environment and untreated culture medium (no salt addition, high food). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…In an earlier study, Becks & Agrawal (2010) demonstrated an increased propensity for sex and an increased frequency of occurrence of sexual individuals in spatially heterogeneous compared to homogenous continuous cultures. Adaptation through sustained sexual reproduction may also explain the observation by Scheuerl & Stelzer (2013) who reported undiminished rates of sexual reproduction in B. calyciflorus populations exposed to stressful levels of salinity despite growth conditions selecting for maximum population growth rate. Similarly to Becks & Agrawal (2012), Declerck et al (2015) also observed high rates of sexual reproduction, but only during an episode of population decline at the start of their selection experiment.…”
Section: Rapid Evolution Of Sex and Its Implications For Adaptationmentioning
confidence: 90%
See 2 more Smart Citations
“…In an earlier study, Becks & Agrawal (2010) demonstrated an increased propensity for sex and an increased frequency of occurrence of sexual individuals in spatially heterogeneous compared to homogenous continuous cultures. Adaptation through sustained sexual reproduction may also explain the observation by Scheuerl & Stelzer (2013) who reported undiminished rates of sexual reproduction in B. calyciflorus populations exposed to stressful levels of salinity despite growth conditions selecting for maximum population growth rate. Similarly to Becks & Agrawal (2012), Declerck et al (2015) also observed high rates of sexual reproduction, but only during an episode of population decline at the start of their selection experiment.…”
Section: Rapid Evolution Of Sex and Its Implications For Adaptationmentioning
confidence: 90%
“…Whereas studies on B. plicatilis consistently checked the identity of cryptic species, this has seldom been done in studies with B. calyciflorus (Table 1). With the exception of one study (Scheuerl & Stelzer, 2013), experimental studies always made use of chemostats or semi-continuous batch cultures when exposing populations to experimental selection conditions. Tests of adaptation were most often based on the evaluation of short-term fitness indicators, mainly the intrinsic population growth rate or surrogate variables (e.g., lifetime fecundity) and, more rarely, the outcome of direct competition experiments (Stelzer, 2011) or the capacity to suppress food levels (C*; Declerck et al, 2015).…”
Section: Review Of Studies Using Monogonontsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Differences in saltwater tolerance have been implicated in the stable coexistence of sibling species in cryptic species complexes and local adaptation of aquatic invertebrates such as rotifers (Montero‐Pau & Serra ; Scheuerl & Stelzer ). Rapid evolution of enzymes (V‐type H + ATPase and Na + /K + ATPase) in the copepod Eurytema affinis has been linked with the capacity of this invasive species to move from marine to FW systems (Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Within fishes, salinity tolerance differs both among closely related species and within populations of the same species, with killifish and sticklebacks representing two well-studied examples (Jones et al 2012;Kozak et al 2013). Differences in saltwater tolerance have been implicated in the stable coexistence of sibling species in cryptic species complexes and local adaptation of aquatic invertebrates such as rotifers (Montero-Pau & Serra 2011;Scheuerl & Stelzer 2013). Rapid evolution of enzymes (V-type H + ATPase and Na + /K + ATPase) in the copepod Eurytema affinis has been linked with the capacity of this invasive species to move from marine to FW systems (Lee et al 2011).…”
Section: Introductionmentioning
confidence: 99%